Current state of pre-service teacher training for primary education: A view on the case of Mexico - Cuevas-Cajiga, Yazmín; Moreno-Olivos, Tiburcio (Education Policy Analysis Archives, 2022)
Pre-service teacher training is a concern of various social sectors, and it is a central issue of educational policy in Mexico. The debate, however, has focused on the relevance of teacher-training colleges (the main institutions responsible for this kind of education), as well as on the reforms of their curricula. This gap in the research warrants a greater understanding of the current state of pre-service teacher training for primary education in Mexico through an examination of both local and international literature. The results were organized into five spheres of analysis: professional, educational policy, institution and instructional traditions, curricular, and subjects. After discussing these, we can confirm that the design of educational policies and curricula modifications in pre-service teacher training for primary education require diagnostics and discussions around, among others, the status of the teaching profession, the kind of institutions that offer it and their predominant pedagogical traditions, the prevailing international recommendations, the corps of teacher trainers, and the students who choose teaching as a career path, all towards the creation of actions that consider all the components and subjects involved.